2018
DOI: 10.1177/1477153518756700
|View full text |Cite
|
Sign up to set email alerts
|

Measuring light in field experiments using dummies and objects: A study of concert lighting

Abstract: Lighting experiments were performed in a real context populated with dummies and objects. Using the King's College Chapel in Cambridge as a case study, two field surveys of concert lighting were performed, one with the chapel empty and one with it occupied. In each survey, photometric data were collected under three electric lighting conditions and from six different viewing positions. A comparative analysis indicates that the data gathered from the occupied space represent the luminances more accurately, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…A detailed description of the experimental space and layout has been given in Lo and Steemers. 54
Figure 1Four electric light settings: (a) Setting I, Interim Lighting: Peripheral lights - 4 sets of light fixtures were mounted on the North and South walls. Each set consisted of a Megaman 320 w energy-saving fluorescent lamp (Table 3(c)) and 2 supplementary 16 w Philips MasterLed spotlights (Table 3(d)); (b) Setting II, Interim Plus: Peripheral lights and an overhead spotlight - Setting I + A Megaman 320 w energy-saving fluorescent lamp (Table 3(c)) suspended at 4 m high; (c) Setting III, All Lighting: Peripheral lights, overhead rig lights and an overhead spotlight - Setting I + Setting IV; (d) Setting IV, Rig Lighting (control setting): Overhead rig lights and an overhead spotlight - 28 Havells Sylvania Hi-Spot 95 halogen lights (Table 3(e)) and a Megaman 320 w energy-saving fluorescent lamp (Table 3c)) suspended at 4 m high (see Table 3 for detailed specifications)
…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the experimental space and layout has been given in Lo and Steemers. 54
Figure 1Four electric light settings: (a) Setting I, Interim Lighting: Peripheral lights - 4 sets of light fixtures were mounted on the North and South walls. Each set consisted of a Megaman 320 w energy-saving fluorescent lamp (Table 3(c)) and 2 supplementary 16 w Philips MasterLed spotlights (Table 3(d)); (b) Setting II, Interim Plus: Peripheral lights and an overhead spotlight - Setting I + A Megaman 320 w energy-saving fluorescent lamp (Table 3(c)) suspended at 4 m high; (c) Setting III, All Lighting: Peripheral lights, overhead rig lights and an overhead spotlight - Setting I + Setting IV; (d) Setting IV, Rig Lighting (control setting): Overhead rig lights and an overhead spotlight - 28 Havells Sylvania Hi-Spot 95 halogen lights (Table 3(e)) and a Megaman 320 w energy-saving fluorescent lamp (Table 3c)) suspended at 4 m high (see Table 3 for detailed specifications)
…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…63 Measuring procedures have been presented previously. 54 We processed and analysed the images and photometric data in relation to the observer's visual field, aiming to provide a comprehensive mathematical and spatial analysis of light for the chapel. For this to be achieved, we adopted image zoning and abstraction techniques (Figures 6 and 7): Using binary masks, the images were partitioned based on the structure of the visual field.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A studied revealed that the luminance level in several light booths varied from 100 to >1000 cd/m 2 [11]. There are studies that show how correlated color temperature and illuminance affect color perception [12][13][14][15] and users' feeling [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%